High Frequencies of Caspase-3 Expressing Mycobacterium tuberculosis-Specific CD4+ T Cells Are Associated With Active Tuberculosis - Adekambi, Toidi; Ibegbu, Chris C.; Cagle, Stephanie; Ray, Susan M.; Rengarajan, Jyothi (Frontiers in Immunology, 2018)
Antigen-specific CD4+ T cell responses to Mycobacterium tuberculosis (Mtb) infection are important for host defense against tuberculosis (TB). However, Mtb specific IFN-γ-producing T cells do not distinguish active tuberculosis (ATB) patients from individuals with asymptomatic latent Mtb infection (LTBI). We reasoned that the immune phenotype of Mtb-specific IFN-γ+ CD4+ T cells could provide an indirect gauge of Mtb antigen load within individuals. We sought to identify immune markers in Mtb-specific IFN-γ+ CD4+ T cells and hypothesized that expression of caspase-3 Mtb-specific CD4+ T cells would be associated with ATB. Using polychromatic flow cytometry, we evaluated the expression of caspase-3 in Mtb-specific CD4+ T cells from LTBI and ATB as well as from ATB patients undergoing anti-TB treatment. We found significantly higher frequencies of Mtb-specific caspase-3+IFN-γ+ CD4+ T cells in ATB compared to LTBI. Caspase-3+IFN-γ+CD4+ T cells were also more activated compared to their caspase-3-negative counterparts. Furthermore, the frequencies of caspase-3+IFN-γ+ CD4+ T cells decreased in response to anti-TB treatment. Our studies suggest that the frequencies of caspase-3-expressing antigen-specific CD4+ T cells may reflect mycobacterial burden in vivo and may be useful for distinguishing Mtb infection status along with other host biomarkers.